Cognitive impairment in patients after traumatic brain injury - Ratanalert, Sanguansin; Assanangkornchai, Sawitri; Seahang, Sakchai; Oewakul, Thakul (Thai Journal of Neurological Surgery, 2025)
Cognitive deficit after traumatic brain injury (TBI) was prospectively studied in patients admitted in Songklanagarind Hospital during January 2010 to December 2013. At discharge, 187 out of 521 cases had cognitive deficit, as defined by an MMSE score <23. Thirty cases of this group were not scheduled for follow up due to routine post-treatment neurological examinations were unremarkable. This finding emphasizes the importance of cognitive measurements such as the MMSE in TBI patients, and can assist health care teams to add appropriate information and suggest appropriate interventions to patients and their families.